Scleractinian Diversity Of Ritchieas Archipelago, Andaman & Nicobar Islands (Global Journal of Science Frontier Research, 2012)
Ritchie's Archipelago, being the part of South Andaman, shows a variety of marine biodiversity in each of its thirteen islands. These islands show a great deal of scleractinian life on its continental shelf in a fringing pattern. The study will help up to get a summarized data of scleractinian diversity of this archipelago. The will be to take conservatory measure for the proper sustainable development of coral reef of the islands. A Total of 168 species of scleractinian corals were recorded during the study period from the study areas. Shannon -Weaver Diversity index (H¯) of Scleractinian corals ofthe islands was recorded between 4.718 and 6.556, indicating very high coral diversity of those places. Similarity index (S) was also ranges from 29.41% to 73.89%, suggeststhe existence of species strong links between islands. Ritchie's Archipelago is a group of islands which shows a variety of scleractinian corals. high level of species co-existence which harbours with the other associated faunal communities for their survival. The diversity of scleractinian corals in the Ritchie's Archipelago is discussed in detail in this paper.
Keywords: Andaman; Diversity; Ritchie's Archipelago; Scleractinian Coral; Shannon -Weaver Diversity index; Similarity index; Ritchieâ€™s Archipelago; Shannon â€"Weaver Diversity index; Similarity index.